Meningkatkan Daya Saing UMKM melalui Analisis SWOT dan NIB - Hidayat, Taufik; Wulandari, Anna; Mulyanto, Heru; Bastanta, Andreas Riski; Muhsoni, Ridwan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are critical as the backbone of local economies and a source of innovation in this rapidly evolving economic world. MSMEs have great potential but often face problems such as lack of capital, limited market access, and lack of knowledge of business strategies. This activity report discusses the mentoring efforts made to support MSMEs, specifically "Brewman Coffee", in analysing their business SWOT and helping them to create a Business Identification Number (NIB) to support business legality and growth. The goal of this activity is that MSMEs can prepare themselves to face market challenges and better utilise existing opportunities through this mentoring. The methods used were observation, interviews, training and mentoring, and monitoring and evaluation. The activity results show that partners understand the business strategy to be carried out and can make NIB independently. The next activity is expected that partners can continue to manage legality so that they can compete globally.